2007
DOI: 10.1097/opx.0b013e318073c2f2
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity and Fixation Characteristics in Age-Related Macular Degeneration

Abstract: Although the acuity measured under different stimulus conditions varies, the absolute differences are small. This suggests that these techniques would not be helpful in determining fixation characteristics, or predicting the outcome of rehabilitation in individual patients with AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…For reading, a PRL left or right of the scotoma would mean that text letters on the attended line would disappear into the scotoma, so placement of the PRL above or below the scotoma would be advantageous. But 34-60% of patients adopt a PRL left of their scotoma (Guez et al 1993, Fletcher & Schuchard 1997, Cacho et al 2007. Some others have reported that the majority of patients with macular disease, especially those with Stargardt disease, had a PRL below their scotoma (White & Bedell 1990, Reinhard et al 2007, Greenstein et al 2008.…”
Section: Oculomotor and Perceptual Plasticitymentioning
confidence: 99%
“…For reading, a PRL left or right of the scotoma would mean that text letters on the attended line would disappear into the scotoma, so placement of the PRL above or below the scotoma would be advantageous. But 34-60% of patients adopt a PRL left of their scotoma (Guez et al 1993, Fletcher & Schuchard 1997, Cacho et al 2007. Some others have reported that the majority of patients with macular disease, especially those with Stargardt disease, had a PRL below their scotoma (White & Bedell 1990, Reinhard et al 2007, Greenstein et al 2008.…”
Section: Oculomotor and Perceptual Plasticitymentioning
confidence: 99%
“…Both groups showed the expected increase of crowding with increased eccentricity. Recently, Cacho and co‐worker 59 found that subjects with ARMD exhibited only a small crowding effect, which was not greater than that documented in subjects with normal vision. We can conclude that early ARM does not increase contour interaction and that the increased crowding that has been documented in ARMD 11,60 may be because an eccentric retinal location is used for fixation, at which there is more crowding than at the fovea 43,61,62 .…”
Section: Discussionmentioning
confidence: 84%
“…These normality values should be checked in the patients with doubt central vision diagnosis as age-related macular degeneration [58], multiple sclerosis neuropathy [59], diabetic retinopathy [37], intoxications [20] and for a more controlled study of the early foveal involvement in glaucoma patients [51].…”
Section: Discussionmentioning
confidence: 99%